ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN PENERAPAN RENDAM KAKI DENGAN AIR HANGAT CAMPUR KENCUR UNTUK MENGURANGI EDEMA KAKI - Pratiwi Dwi Handayani; Mariyana; Astri Yunifitri; Tri Ribut Sulistyawati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Edema occurs in about 80% of pregnancies. Edema occurs due to pressure on the uterus which inhibits venous return and the pull of gravity causes greater fluid retention. Soaking the feet using warm water mixed with kencur is used to soak the feet or hydrotherapy for pregnant women. The aim of the research is to provide midwifery care to pregnant women by applying a foot soak using warm water mixed with kencur to reduce edema on the feet. using a descriptive observational design with a case study approach. Midwifery care was carried out at the Tanjung Balai Karimun Health Center, for Mrs. B. Management of soaking therapy in warm water mixed with kencur was carried out for 4 consecutive days, for 15 minutes. Evaluation of the results of the action shows that soaking the feet using warm water mixed with kencur can reduce edema in the feet of TM III pregnant women. It is hoped that this can add insight and experience in conducting midwifery care by applying the method of soaking feet using warm water mixed with kencur to reduce edema on the feet of pregnant women.